2000
DOI: 10.1002/(sici)1097-4628(20000328)75:13<1585::aid-app4>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of jute fibers and interface strength with an epoxy resin

Abstract: Four different forms of jute fibers, namely untreated jute filament (UJF), sliver jute filament (SJF), bleached jute filament (BJF), and mercerized jute filament (MJF), have been subjected to tensile strength analysis following Weibull's theory. The MJF and BJF were obtained by the chemical modification of the UJF. A minimum of 50 fibers of each type, at three different gauge lengths, i.e., 15, 30, and 50 mm, were used to study the strength distribution and the effect of gauge length. The mean fiber strength w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 30 publications
5
29
0
Order By: Relevance
“…2 illustrates that and tthe longer the fibre, the more chance there is for a weak link where the fibre can break at a certain load [1]. The tensile strength is described through the Weibull distribution by a lot of scientists [2,3]. The use of this distribution can be defended if the strength is controlled by the presence of critical flaws and if the material is brittle.…”
Section: Probability Of Breakingmentioning
confidence: 99%
“…2 illustrates that and tthe longer the fibre, the more chance there is for a weak link where the fibre can break at a certain load [1]. The tensile strength is described through the Weibull distribution by a lot of scientists [2,3]. The use of this distribution can be defended if the strength is controlled by the presence of critical flaws and if the material is brittle.…”
Section: Probability Of Breakingmentioning
confidence: 99%
“…This work presents a process that increases the hydrophobicity of the fibers while respecting the environment (no solvent used) and is economically viable in terms of energy and equipment (no heating required). The main objectives of this study are (1) to evaluate the effect of acetylation time on the cellulosic fibers structure and (2) to study the influence of this chemical treatment on the wettability of fibers in order to evaluate their affinity with epoxy resins frequently used in composite materials. For this purpose, flax, Kraft, and thermomechanical pulp fibers were acetylated in a heterogeneous reaction environment, for different reaction times at room temperature and the structural modification of lignocellulosic fibers have been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Tripathy et al 180 used the single fibre fragmentation test for determining the critical fibre length and IFSS of jute fibre reinforced epoxy composites. In an interesting study, Valadez-Gonzalez et al 181 have shown that there is a maximum quantity of silane coupling agent that can be deposited on henequen fibre.…”
Section: Fragmentation Test/single Fibre Composite (Sfc) Testmentioning
confidence: 99%